Development in the Field Of Technology for Cooperative Problem Solving Utilizing Non-Conventional Energy Resources in India & Future Trend (International Journal of Scientific Research and Management (IJSRM), 2017)
Cooperative problem solving is the key to effective and efficient energy management. Energy is the reward of nature to people. Meeting massive demand of power is a major issue and a concern. Hence, the concept of cooperative problem solving can be effectively applied by bringing various public and private sector together to mitigate the problems. The main focus of this paper is the application of cooperative problem solving technique to provide an efficient solution to rising demand for power. It shall apply qualitative and quantitative computational approach. This paper illustrates on various sources of renewable energies available in India and developments in technology for utilizing this resource. It also focuses on present energy demand and future need for energy by evaluating India’s energy demand with the growing technology development in the renewable energy sector.